The PEMANFAATAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) DALAM MENENTUKAN PRIORITAS PENANGANAN PERBAIKAN JALAN PADA SKPD-TP DINAS PEKERJAAN UMUM PROVINSI JAMBI - Budiarti, Rike Limia; Putra, Arya (Lembaga Penelitian dan Pengabdian Masyarakat - STMIK Nurdin Hamzah Jambi, 2018)
Organizing fund from deconcentration fund and / or fund of assistance task to conduct development activities, development, and bridge in kelolah by SKPD-TD Public Works Department of Jambi Province which directly responsible to Governor. The amount of data needed to be recorded will cause the length of process analysis, process and produce data that is less accurate, the current road measurement process still using manual calculation process with archiving in the form of printed documents. while the funding that tried the government is limited. The problem of handling the long road of the national road while the Budget has not been proportional through the SKPD-TP of the Public Works Department of Jambi Province should prioritize which roads should indeed improve first. To discuss the above problem, then the solution for Decision Support System (SPK) determination of road improvements. Many problems can be released by using Decision Support System (SPK), a method that can be used in the process of SPK Analytical Hierarchy Process Analysis (AHP). This application is built with Visual Basic 2010, Crystal Report 10